Predictors of delinquency among adolescents of divorced families - Esmaeili, Nooshin Sabour; Yaacob, Siti Nor; Juhari, Rumaya (Canadian Center of Science and Education, 2013)
Although delinquency is universal, few studies examined it from an Asian perspective, and even fewer considered adolescents of divorced families in Iran. The current study examined whether correlates of delinquency among western adolescents are similarly effective for predicting delinquency among adolescents from divorced families in the Mashhad city in Iran. Post-divorce parental conflict, maternal distress, economic hardship and parent-child relationship were regressed against delinquency. The parent-child relationship was the strongest significant predictor of self-reported delinquency.